Creativity: a driving force behind yield management / Muhammad Shahbaz Shabbir and Amjad Shamim - Shabbir, Muhammad Shahbaz; Shamim, Amjad (2010)
The ultimate focus of an enterprise is to earn handsome revenue for which different strategies are developed and used by the organizations. A big challenge which service organizations are facing is the factor of perishability where on one side they have to keep the customers happy and on the other they have to achieve their targets. Hotel industry is one of the most sensitive industries where customers are more time sensitive giving a good sign to the managers for maximization of revenue. By taking the advantage of the time, creative managers emphasize on the revenue/yield maximization. This study is conducted to explore the impact of creativity on yield management in hotel industry of Pakistan. Quantitative data approach was used and data was gathered through close-ended questionnaire by using stratified sampling technique from 128 professionals (sample size) working in five stars, four stars and three stars hotels in Islamabad and Rawalpindi, Islamic Republic of Pakistan. Findings indicate that the overall creativity has a significant impact on yield management and creativity is likely to be emerged if employees are given a tension free environment, support by the management, rewards against successive creative ideas and opportunity for ideas sharing. Since hotel industry in Pakistan is undergoing a process of increased competition, therefore, the adoption and implementation of yield management is identified as a very essential tool for survival. It has also been observed that, for proper yield management implementation, hotel industry needs to focus on employees’ creativity.